(3QSGdI aj BOGH GdHMK hWQb GdefGXQIs - (3eMeO Hf CTQa GdMSjfj GdSeQbfOj,J (B600 (3g` s
(3ChdgG (B:s
(3HSe Gddg GdQMef GdQMje GdMeO ddg QH GdYGdejf hHYO abO bGd ehdGfG TeS GdedI hGdOjf eMeO SeQbfOi gPg QSGdI ai BOGH GdHMK hWQb GdefGXQI GdJi jMJGL EdjgG cd eJYde hbHd GdJYde hGdJYdje s
(3BNQgG (B:s
(3hEf de jcf Pdc dGJbOjQ KGHJkG ai GdCRd jdRe KHhJ GdYdjI hEdG jdRe EQJaGY GdfbjVjf Hg jMUd GdebUhO ceG eQ ai GdTb GdChd ef GdJQOjO GdePchQ hGddg CYde HGdUhGH hEdjg GdeQLY hGdeBH s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3cJHJ HYV GdcdeGJ HGdMeQIs
(3bQf GdfSN (B:s
(3GdbQf GdMGOj YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
Keywords: (3GdJhMjO hGdedd hGdfMds